Properties of chitosan-gelatine based, aloe vera and propolis added biofunctional wound dressing material - Akkad, Haya; Ciftci, Fatih; Erarslan, Azime; Ozerol, Esma Ahlatcioglu (TAYLOR & FRANCIS LTD, 2026)
This study describes the development and characterization of a multilayered wound dressing composed of a chitosan (CHI), gelatin (GEL), and Aloe vera (AV) base layer integrated with electrospun polyvinyl alcohol (PVA)/propolis nanofibers (WD3). FE-SEM analysis showed a bead-free porous network with a mean fiber diameter of 185 +/- 24 nm. XRD and DSC results confirmed the semi-crystalline structure and thermal stability of the scaffolds, with the WD1 baseline exhibiting a crystalline peak at 2 theta = 26.070. Mechanical analysis demonstrated that the optimized WD3 formulation possesses a high dry tensile strength of similar to 49 MPa, which transitions into a highly conformable and flexible hydrogel state upon hydration, reaching a peak elongation at break of 68.4%. Swelling and degradation studies highlighted a superior fluid absorption capacity of 97% and a controlled mass loss of 18% over 7 hours, ensuring effective exudate management and structural longevity. Standardized LC-MS/MS fingerprinting of the propolis extract (TPC: 199.7 mg GAE/g) identified key polyphenols, including pinocembrin and galangin, which governed a sustained release profile following the Korsmeyer-Peppas model (n = 0.62). Biological assays confirmed that the WD3 group supported cell viability with a metabolic activity rate of 110.7% and provided antioxidant activity with an IC50 of 16.31 & micro;g/mL. Furthermore, antibacterial tests showed an inhibition zone of 23.6 +/- 2.1 mm against S. aureus. These results indicate that the multilayered CHI/GEL/AV/PVA/Propolis dressing provides the structural and biological properties necessary for potential applications in wound care.
Keywords: Wound dressing; burn treatment; PVA; chitosan; aloe vera; propolis; ACID PHENETHYL ESTER; CAFFEIC ACID; HYDROGELS; NANOFIBERS; Engineering; Materials Science; Polymer Science